Electron concentration effects on the Shastry-Sutherland phase stability in Ce2-xPd2+yIn1-z solid solutions - Sereni, J.G.; Giovannini, M.; Gómez Berisso, M.; Saccone, A.; Sereni, Julián (American Physical Society, 2011)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina